Assessment of the status of emergency obstetric care services in primary health-care centers in selected local government areas of Rivers State, Nigeria - Ishmael D Jaja; Michael Promise Ogolodom (Wolters Kluwer Medknow Publications, 2023)
Background: Reducing maternal and neonatal mortality and morbidity are major public health concern globally and demands policies and commitments, strategy formulations and implementation and improved health-care service delivery and management. This study aimed to evaluate the status of emergency obstetric care (EmOC) services in primary health care centers in selected local government areas of Rivers State, Nigeria. Materials and Methods: This was a cross-sectional questionnaire-based study, which was conducted among primary health-care workers in Rivers State, Nigeria. Data obtained were analyzed using both descriptive and inferential statistics. Results: Among the participants in the intervention group, 72 (79.1%) were females, while 19 (20.9%) were males. In the control group, 67 (78.8%) were females, while 18 (21.2%) were males. There was no statistically significant difference between the intervention and the control groups as regards sex (χ2 = 0.0023; P = 0.96). There was no statistically significant difference in the marital status of the participants between the intervention and control groups (χ2 = 0.81; P = 0.93). Midwives/nurses were highest in number with 32 (35.2%) and 27 (31.8%) in the intervention and control groups, respectively, and the least were health attendants with 6 (6.6%) and 7 (8.2%) in the intervention and control groups, respectively. There was no statistically significant difference between participants in the intervention and control groups (χ2 = 1.05; P = 0.96). Conclusions: This study revealed that of all the EmOC signal functions, administration of antibiotics, and oxytocics were the most performed. This study revealed a nonperformance of other signal functions, namely administration of parenteral anticonvulsants for preeclampsia and eclampsia using magnesium sulfate, removal of retained products, assisted vaginal delivery using vacuum extraction or forceps delivery, blood transfusion, and surgery.